The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/mec.12908
|View full text |Cite
|
Sign up to set email alerts
|

A hyperparasite affects the population dynamics of a wild plant pathogen

Abstract: Assessing the impact of natural enemies of plant and animal pathogens on their host's population dynamics is needed to determine the role of hyperparasites in affecting disease dynamics, and their potential for use in efficient control strategies of pathogens. Here, we focus on the long-term study describing metapopulation dynamics of an obligate pathogen, the powdery mildew (Podosphaera plantaginis) naturally infecting its wild host plant (Plantago lanceolata) in the fragmented landscape of the Åland archipel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 44 publications
0
30
0
Order By: Relevance
“…Here, hyperparasitism significantly reduced the production of overwintering structures. This may explain why previous studies have found a link between hyperparasitism and powdery mildew extinction risk in nature (Tollenaere et al., ). Combined, our results suggest that top‐down control of pathogens by natural enemies may be sensitive to both the combination of pathogen and host genotype, and the specific pathogen life‐history stage that is targeted.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, hyperparasitism significantly reduced the production of overwintering structures. This may explain why previous studies have found a link between hyperparasitism and powdery mildew extinction risk in nature (Tollenaere et al., ). Combined, our results suggest that top‐down control of pathogens by natural enemies may be sensitive to both the combination of pathogen and host genotype, and the specific pathogen life‐history stage that is targeted.…”
Section: Discussionmentioning
confidence: 99%
“…Field surveys have shown that Ampelomyces infections are detectable early during mildew epidemics (Parratt et al., and Supporting Information Figure ), and severely reduce overwinter survival of Po. plantaginis in nature (Tollenaere et al., ). In other mildew species, Ampelomyces reduces conidial production and reverses mildew‐derived tissue damage in hosts under controlled conditions (Abo‐Foul, Raskin, Sztejnberg & Marder, ; Falk, Gadoury, Pearson & Seem, ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…fungi that parasitize other fungi, are commonly found in most terrestrial ecosystems, the best known species being those that attack fungal plant pathogens [1][2][3][4] . A number of mycoparasites have been long studied and commercially utilized as biocontrol agents (BCAs) of crop pathogens 3,4 ; others have been in focus as components of natural multitrophic relationships 2,[5][6][7][8][9] . Direct observation of interfungal parasitic relationships is notoriously difficult at cellular or hyphal level, using classical light, scanning and transmission electron microscopy (LM, SEM and TEM) and other visualization methods 1,[10][11][12][13] .…”
Section: Introductionmentioning
confidence: 99%